Preliminary cytotoxic activity of different extracts of Averrhoa bilimbi (fruits) - Ali, Md. Ramjan; Hossain, Marjan; Runa, Jannatul Ferdous; Hasanuzzaman, Md. (International Current Pharmaceutical Journal, 2013)
The crude methanolic extract of Averrhoa bilimbi Linn. (Oxalidiaceae) fruits and its different fractions have been investigated for the evaluation of in vitro cytotoxic potential. The dried and powder fruits were extracted with methanol at room temperature and the concentrated methanolic extract was fractionated by the modified Kupchan partitioning method to provide pet-ether, carbon tetrachloride, chloroform and aqueous soluble fractions. Brine shrimp (Artemia salina) lethality bioassay was used to investigate the cytotoxic potential of A. bilimbi. Compared to vincristine sulfate (with LC50 of 0.839 µg/ml) methanolic extract, carbon tetrachloride and pet-ether soluble fractions demonstrated a significant cytotoxic potential (having LC50 of 0.005µg/ml, 1.198µg/ml and 0.781µg/ml, respectively). The LC50 values of chloroform and aqueous soluble fractions were 5.691µg/ml and 6.123µg/ml, respectively. This study reveals that A. bilimbi possesses effective cytotoxic properties and hence can be a potential source for the isolation of active principle(s) for cancer therapy. DOI: http://dx.doi.org/10.3329/icpj.v2i3.13634 International Current Pharmaceutical Journal, February 2013, 2(3): 83-84